Development and effect verification of a stress management program for dementia care staff - Narumoto, Jin; Fujita, Yu; Sato, Shinichi; Oba, Hikaru (Japanese Journal of Clinical Geropsychology, 2021)
The present study aimed to develop a stress management program focusing on sleep hygiene, time management, interpersonal relationships with colleagues, and ability to cope with patients’ behavioral and psychological symptoms of dementia, as well as to investigate the effect of the program on the mental health of dementia care staff. We developed this program based on previous findings and the exchange of opinions among professionals, such as clinical psychologists and certified care workers. Effect verification was conducted with 49 care staff (intervention group: 25, control group: 24) working in 11 long-term care facilities in Kinki region. A two-way ANOVA revealed no significant difference in main effect and interaction. To confirm the program’s effect, further studies are needed considering aspects such as an appropriate sample size, intervention duration, and outcome evaluation method.